Analisis Hermeneutika Yuridis Pasal 239 Ayat (2) Huruf D dan G Undang-Undang No.17 Tahun 2014 - Utari, Anak Agung Adik Sri; Rumiartha, I Nyoman Prabu Buana (Advances In Social Humanities Research, 2024)
Article 239 paragraph (1) and paragraph (2) of the MD3 Law regulates the right of political parties to conduct inter-term dismissal (PAW) of DPR members. However, the ambiguity in Article 239 paragraph (2) letters d and g caused controversy because the terms of PAW became unclear and often misused to resolve internal party conflicts. This study aims to analyze the juridical hermeneutics of the provisions of Article 239 paragraph (2) letter d and g of Law Number 17 of 1014 concerning MPR, DPR, DPD, and DPRD. The results showed that abstract interpretations of the phrases "proposed by political parties" and "statutory provisions" open up opportunities for subjectivity in dismissing DPR members. Therefore, the recalling arrangement of DPR members requires further clarification to address the abstract issue of interpretation.